Cysticercus fasciolaris in Brown Rats (Rattus norvegicus) in Grenada, West Indies - Ravindra Sharma; Keshaw Tiwari; Kristen Birmingham; Elan Armstrong; Andrea Montanez; Reneka Guy; Yvette Sepulveda; Veronica Mapp-Alexander; Claude DeAllie (Journal of Parasitology Research)
Cat is the definitive host of Taenia taeniaeformis (T. taeniaeformis). Cysticercus fasciolaris (C. fasciolaris), the larval stage of T. taeniaeformis, develops in small rodents which act as intermediate host. The aim of this study was to estimate the prevalence of C. fasciolaris in brown rats (Rattus norvegicus) in the densely human populated parishes, St. George’s and St. David’s of Grenada, West Indies. One hundred and seventy rats were trapped near the residential areas from May to July, 2017 and examined for C. fasciolaris in their liver. Of the 170 rats 115 (67.6%, CI 95% from 60.1 to 74.6) were positive for the larval stage of T. taeniaeformis. One to three cysts were observed in each liver, containing a single larva in each cyst. The prevalence was 77.9% in St. George and 59.1% in St. David which is a significant difference (p<0.05) between the two parishes under study. Based on gender, prevalence in males was 60.9% and females 74.7%. Significant difference was observed between young and adult rats (p=0.03). Prevalence in young rats was 45.0% compared to adults (70.7%). Further study of risk assessment in the cat population in areas of the present research is strongly suggested.